Otonomi Daerah dan “Amandemen Kedua” UUD 1945 - Rawinarno, Tjahyo (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2017)
Since its inception, many parties expect much that regional autonomy will be one of the gateways that bring Indonesian society to prosperity and prosperity. The current local autonomy raises the issue of where regional heads can’t cooperate with the regional heads above because they feel the same or equal to the governor and the number of corruption cases perpetrated by the regional head. The implementation of decentralization and deconcentration has not been able to significantly change the welfare of the people in the region. Implementation of local autonomy is still far from the ideals that have been established together. The implementation of regional autonomy requires the improvement of the legal constitution, especially the second amendment Constitution of the Republic of Indonesia. In keeping with the principle of granting greater authority to the regions to manage and prosper itself, it will be far more effective than providing central government obligations to distribute welfare.